Engaging communities through civic engagement in art museum education - Bobick, Bryna 1974-; DiCindio, Carissa (IGI Global, Publisher of Timely Knowledge, 2021)
"This book features a broad range of museum education experiences that will appeal to a wide audience and will demonstrate the wide-reaching benefits of including these experiences into art education courses" - Provided by publisher
Keywords: Art museums / Educational aspects; Museum outreach programs; Museumspädagogik; Soziale Verantwortung; Kunsterziehung; Aufsatzsammlung